Investigation on fabrication of silicon nanopores using an electrochemical passivation etch-stop strategy - Hao Hong; Xin Lei; Jiangtao Wei; Wenjun Tang; Minjie Ye; Jianwen Sun; Guoqi Zhang; Pasqualina M. Sarro; Zewen Liu (Microsystems & Nanoengineering)
Abstract The three-step wet etching (TSWE) method has been proven to be a promising technique for fabricating silicon nanopores. Despite its potential, one of the bottlenecks of this method is the precise control of the silicon etching and etch-stop, which results in obtaining a well-defined nanopore size. Herein, we present a novel strategy leveraging electrochemical passivation to achieve accurate control over the silicon etching process. By dynamically controlling the oxide layer growth, rapid and reliable etch-stop was achieved in under 4 s, enabling the controllable fabrication of sub-10 nm silicon nanopores. The thickness of the oxide layer was precisely modulated by adjusting the passivation potential, achieving nanopore size shrinkage with a precision better than 2 nm, which can be further enhanced with more refined potential control. This scalable method significantly enhances the TSWE process, offering an efficient approach for producing small-size silicon nanopores with high precision. Importantly, the precise etching control facilitated by electrochemical passivation holds promise for the cost-effective production of high-density, air-insulated monolithic integrated circuits.